Solar electric ambulance van unfolding medical emergencies of rural Bangladesh - Tarek, R.; Anjum, Adiba; Hoque, Md Ashiqul; Azad, Akm M.M.Abdul Malek (© 2016 IEEE, 2018)
This conference paper was published in the IEEE Region 10 Conference, TENCON 2016; Marina Bay SandsSingapore; Singapore; 22 November 2016 through 25 November 2016 [© 2016 IEEE] and the definite version is available at : http://doi.org/10.1109/GHTC.2016.7857328 The Journal's website is at: https://ieeexplore.ieee.org/document/7857328/